Research trends on chemotherapy induced nausea and vomiting: a bibliometric analysis - Ning, Chunhui; Yan, Yunzi; Wang, Yansong; Li, Rui; Liu, Wenjie; Qiu, Linjie; Sun, Lingyun; Yang, Yufei (Frontiers in Pharmacology, 2024)
Background: CINV is a frequent adverse response to cancer treatment. There is still much to learn about the pathophysiology and initiating event of CINV, which necessitates continued research despite decades of effort. Identifying the current foci of the complex disease and assessing the scientific impact of pertinent study are made more difficult by the abundance of publications on CINV. Therefore, our goals in this article are to evaluate developments in this field, examine patterns in research domains, and gauge the expansion of CINV research production globally. Methods: Articles about CINV published between 2012 and 2022 were found by searching the Web of Science Core Collection of Clarivate Analytics. The number of publications over time was visualized using Microsoft Office Excel 2019. CiteSpace and VOSviewer were utilized to create knowledge maps that analyzed collaborations between nations, organizations, and writers. They also presented the history of CINV research and highlighted its current areas of focus. Results: In this study, 846 papers in all were assessed. Most publications (237, 28.01%) came from the USA. University of Toronto was the most productive institution (34, 4.01%). With 25 articles published, or 2.96% of the total, Aapro Matti published the most. The most frequently published journal was found to be Supportive Care (158, 18.68%). “Palonosetron,” “Moderately emetogenic chemotherapy,” “5-HT3 receptor antagonist,” and “Neurokinin 1 receptor antagonists” were considered the hot topics. It can be seen that the research focus is on the drug treatment of chemotherapy-induced nausea and vomiting. Conclusion: Through bibliometric analysis, we were able to gain profound insights into CINV research for the first time. Researchers looking to uncover research frontiers and comprehend important information in this discipline may find the study's findings useful.